Effects of Melatonin on the Passive Mechanical Response of Arteries in Chronic Hypoxic Newborn Lambs - Garcia-Herrera, C; Rivera-Mancilla, E (Elsevier Ltd, 2020)
Chronic hypoxia is a condition that increases the cardiovascular complications of newborns gestated and born at high altitude (HA), over 2500 m above sea level (masl). A particularly complex pathology is pulmonary arterial hypertension of the neonate (PHN), which is increased at HA due to hypobaric hypoxia. Basic and clinical research have recognized that new treatments are needed, because current ones are, in general, palliative and with low effectiveness. Therefore, recently we have proposed melatonin as a potential adjuvant treatment to improve cardiopulmonary function. However, melatonin effects on the mechanical response of the arteries and their microstructure are not known. This study assesses the effects of a neonatal treatment with daily low doses of melatonin on the passive biomechanical behavior of the aorta artery and main pulmonary artery of PHN lambs born in chronic hypobaric hypoxia (at 3600 masl). With this purpose, ex-vivo measurements were made on axial stretch, tensile and opening ring tests together with a histological analysis to explore the morphometry and microstructure of the arteries. Our results show that the passive mechanical properties of the aorta artery and main pulmonary artery of lambs do not seem to be affected by a treatment based on low melatonin doses. However, we found evidence that melatonin has microstructural effects, particularly, diminishing cell proliferation, which is an indicator of antiremodeling capacity. Therefore, the use of melatonin as an adjuvant against pathologies like PHN would present antiproliferative effect at the microstructural level, keeping the macroscopic properties of the aorta artery and main pulmonary artery. © 2020 Elsevier Ltd